THE ROLE OF PSYCHOLOGY IN ACHIEVING HIGH RESULTS IN SPORT - A.E.Oblakulov (Western European Studies, 2024)
This article explores the essential role of psychology in enhancing athletic performance and achieving high results in sports. It emphasizes key psychological factors such as mental toughness, motivation, confidence, and stress management. The article highlights the importance of intrinsic motivation and effective goal setting, using frameworks like SMART to guide athletes in setting achievable objectives. It also discusses the concept of mental toughness and provides practical strategies for developing resilience and focus through visualization and positive self-talk. Additionally, the article addresses the significance of selfefficacy in building confidence and offers techniques for managing performance anxiety, such as mindfulness and relaxation exercises. By integrating these psychological principles, athletes, coaches, and sports organizations can foster an environment conducive to peak performance and overall well-being. The article serves as a comprehensive resource for those looking to enhance their understanding of the psychological aspects of sports performance
Keywords: psychology; self-efficacy; stress management